2017
DOI: 10.3389/fmicb.2017.01245
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of Coccidial Common Antigen Glyceraldehyde 3-Phosphate Dehydrogenase (GAPDH) against Challenge with Three Eimeria Species

Abstract: Coccidiosis is an intestinal disorder of poultry and often caused by simultaneous infections of several Eimeria species. GAPDH is one of the immunogenic common antigens among Eimeria tenella, E. acervulina, and E. maxima identified in our previous study. The present study was performed to further evaluate its immunogenicity and protective efficacy. The genes of GAPDH cloned from E. acervulina and E. maxima were named as EaGAPDH and EmGAPDH, respectively. The immunogenicity of recombinant proteins of EaGAPDH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…The presence of upregulated immunogenic PP2C suggests that PP2C is a potential vaccine candidate for toxoplasmosis [40]. As a common antigen of Eimeria, GAPDH could induce strong humoral and cellular immune responses, and had effective protection against E. tenella, E. acervulina and E. maxima as a potential vaccine candidate [41]. In our present study, GAPDH as an immunodominant antigen was confirmed to be immunologically shared by all three Eimeria species.…”
Section: Discussionsupporting
confidence: 68%
“…The presence of upregulated immunogenic PP2C suggests that PP2C is a potential vaccine candidate for toxoplasmosis [40]. As a common antigen of Eimeria, GAPDH could induce strong humoral and cellular immune responses, and had effective protection against E. tenella, E. acervulina and E. maxima as a potential vaccine candidate [41]. In our present study, GAPDH as an immunodominant antigen was confirmed to be immunologically shared by all three Eimeria species.…”
Section: Discussionsupporting
confidence: 68%
“…In this case, CD8α was significantly downregulated in the intestine of Ross 308 broilers at 6d pi with both infectious doses and CD4 expression was upregulated significantly less, at 13d pi, compared to Ranger Classic broilers. A study by Hong et al reported that E. maxima infection increased both CD8 and CD4 expression at 6‐8 days pi and both CD4 and CD8 lymphocytes numbers, which may have occurred via recognition of antigens such as those encoded by E. maxima surface antigen genes or Eimeria glyceraldehyde‐3‐phosphate dehydrogenase . However, the genotype of these chickens was not reported but the result probably reflects the use of a different genotype to the ones we have used and further highlights the importance of genetic background when extrapolating data between different studies of Eimeria infection in chickens.…”
Section: Discussionmentioning
confidence: 79%
“…Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was performed to detect the puri ed rEmROM2. The rat anti-rEmROM2 serum was prepared by the protocol previously described [8] for the detection of Western blot. Meanwhile, the serum from noninjected rat was used as a negative control.…”
Section: Preparation Of Remrom2 and Anti-remrom2 Serummentioning
confidence: 99%
“…Chicken anti-E. maxima serum was obtained by the method previously described [8,20]. A Western blot assay was carried out with the above chicken antiserum as primary antibody (serum from uninfected chicken was set as negative control), and horseradish peroxidase (HRP)-conjugated goat anti-chicken IgG (Sigma-Aldrich, Darmstadt, Germany) as secondary antibody.…”
Section: Western Blot Recognition Of Remrom2 By Chicken Anti-e Maximmentioning
confidence: 99%
See 1 more Smart Citation